Prevalence of Orofacial Clefts in Nigeria. (May 2014) - Butali, A.; Adeyemo, W.L.; Mossey, P.A.; Olasoji, H.O.; Onah, I.I.; Adebola, A.; Akintububo, A.; James, O.; Adeosun, O.O.; Ogunlewe, M.O.; Ladeinde, A.L.; Mofikoya, B.O.; et al.
Orofacial clefts are the most common malformations of the head and neck. In Africa, orofacial clefts are underascertained, with little or no surveillance system in most parts for clefts and other birth defects. A Nigerian craniofacial anomalies study, NigeriaCRAN, was established in 2006 to support cleft research specifically for epidemiological studies, treatment outcomes, and studies into etiology and prevention. We pooled data from seven of the largest Smile Train treatment centers in the six geopolitical zones in Nigeria. Data from September 2006 to June 2011 were analyzed and clefts compared between sides and genders using the Fisher exact test. A total of 2197 cases were identified during the study period, with an estimated prevalence rate of 0.5 per 1000. Of the total number of orofacial clefts, 54.4% occur in males and 45.6% in females. There was a significant difference ( P =.0001) between unilateral left clefts and unilateral right clefts, and there was a significant difference ( P =.0001) between bilateral clefts and clefts on either the left or right side. A significant gender difference ( P =.03) was also observed for cleft palate, with more females than males. A total of 103 (4.7%) associated anomalies were identified. There were nine syndromic cleft cases, and 10.4% of the total number of individuals with clefts have an affected relative. The significant difference between unilateral clefts and the gender differences in the proportion of cleft palate only are consistent with the literature. The present study emphasizes the need for birth defects registries in developing countries in order to estimate the exact prevalence of birth defects including orofacial clefts.